Unraveling the chloroplast genome of Actiniopteris radiata from Saudi Arabia: Insights into genetic diversity in Pteridaceae - Fatmah Ahmed SAFHI; Salha Mesfer ALSHAMRANI (Notulae Botanicae Horti Agrobotanici Cluj-Napoca)
This study reports the chloroplast genome sequence of Actiniopteris radiata from Jazan, Saudi Arabia, marking it as the inaugural fern species of the Actiniopteris genus to be sequenced and analyzed. The chloroplast genome spans 148,219 bp with a GC content of 40.8% and contains 131 genes: 87 protein-coding genes (PCGs), 36 transfer RNAs (tRNAs), and 8 ribosomal RNAs (rRNAs). Comparative analyses with nine related species revealed a genome size range from 148,219 bp (A. radiata) to 154,106 bp (Pteris vittata), with GC content spanning 36.7% (Ceratopteris cornuta) to 44.4% (Adiantum shastense). The analysis identified 538 simple sequence repeats (SSRs) concentrated in the large single-copy (LSC) region. Codon usage analysis showed significant preferences, including an RSCU value of 0.36 for GCT in alanine codons. SNP analysis revealed 25,137 SNPs across the genome, yielding a dS/dN ratios indicative of purifying selection. Notable genes, such as psbD and psaA, exhibited high dS/dN ratios (46 and 8, respectively), suggesting adaptive evolution in photosynthetic pathways. Phylogenetic analysis confirmed the distinct evolutionary position of A. radiata within the Pteridoideae subfamily, highlighting its unique lineage in the absence of close relatives in existing databases. This research establishes a foundational resource for understanding fern evolution in the Pteridaceae family.